2010
DOI: 10.1038/onc.2010.92
|View full text |Cite
|
Sign up to set email alerts
|

TWISTing an embryonic transcription factor into an oncoprotein

Abstract: Over the past decade, the reactivation of TWIST embryonic transcription factors has been described as a frequent event and a marker of poor prognosis in an impressive array of human cancers. Growing evidence now supports the premise that these cancers hijack TWIST's embryonic functions, granting oncogenic and metastatic properties. In this review, we report on the history and recent breakthroughs in understanding TWIST protein functions and the emerging role of the associated epithelialmesenchymal transition (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
145
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(155 citation statements)
references
References 141 publications
10
145
0
Order By: Relevance
“…The important known EMT‐activating TFs, such as ZEB1, ZEB2, SNAIL1, SNAIL2, RUNX2, and ETS1, were all found upregulated, while known negative TF regulators of EMT, such as SMAD3, MITF, and ETF, were all downregulated in postEMT cells in concordance with the literature 16, 17. IPA also identified a number of TFs that did not show significant differential expression changes in postEMT cells but were predicted to be activated or inhibited based on the expression profiles of their target genes.…”
Section: Resultssupporting
confidence: 89%
“…The important known EMT‐activating TFs, such as ZEB1, ZEB2, SNAIL1, SNAIL2, RUNX2, and ETS1, were all found upregulated, while known negative TF regulators of EMT, such as SMAD3, MITF, and ETF, were all downregulated in postEMT cells in concordance with the literature 16, 17. IPA also identified a number of TFs that did not show significant differential expression changes in postEMT cells but were predicted to be activated or inhibited based on the expression profiles of their target genes.…”
Section: Resultssupporting
confidence: 89%
“…The transcriptional mechanisms by which TWIST1 regulates BCL-2 expression has previously been determined (36,37). TWIST1 has been reported to confer chemoresistance by increasing the BCL-2/BAX ratio (36). ARTN increased BCL-2 expression in BT549 cells by transcriptional regulation of the BCL-2 promoter, and siRNA to TWIST1 abrogated ARTN stimulation of the BCL-2 promoter (supplemental Fig.…”
Section: Bcl-2 Is Necessary For Twist1-mediated Artn-stimulated Csc-lmentioning
confidence: 90%
“…S2A). The transcriptional mechanisms by which TWIST1 regulates BCL-2 expression has previously been determined (36,37). TWIST1 has been reported to confer chemoresistance by increasing the BCL-2/BAX ratio (36).…”
Section: Bcl-2 Is Necessary For Twist1-mediated Artn-stimulated Csc-lmentioning
confidence: 99%
“…The basic helix-loop-helix transcription factor Twist1 is known to regulate the expression of target genes and to promote EMT (Ansieau et al 2010). We have previously shown that Twist1 promoted prostate cancer growth through the regulation of AR expression (Shiota et al 2010(Shiota et al , 2014.…”
Section: Introductionmentioning
confidence: 99%